1996
DOI: 10.1002/art.1780390407
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the transcription factor nuclear factor‐κB in human inflamed synovial tissue

Abstract: Objective. The transcription factor–κB (NF‐κB) has been implicated in the inflammatory response and is known to be activated by a process involving reactive oxygen intermediates. The purpose of the present study was to demonstrate the presence and distribution of activated NF‐κB in synovium samples from patients with rheumatoid arthritis (RA) and osteoarthritis (OA) and from autopsy subjects with no known history of arthritis. Methods. Immunohistochemical staining was performed using both polyclonal and monocl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
168
2
5

Year Published

1998
1998
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(187 citation statements)
references
References 33 publications
10
168
2
5
Order By: Relevance
“…Regarding the involvement of the NF-B pathway in RA, the expression of both p50 and p65 in synovial tissue has been reported (54,55). Bondeson et al demonstrated that overexpression of I B␣ significantly inhibited the production of TNF␣ and IL-1␤ by freshly isolated synovial cells (56).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the involvement of the NF-B pathway in RA, the expression of both p50 and p65 in synovial tissue has been reported (54,55). Bondeson et al demonstrated that overexpression of I B␣ significantly inhibited the production of TNF␣ and IL-1␤ by freshly isolated synovial cells (56).…”
Section: Discussionmentioning
confidence: 99%
“…Cell stimulation induces degradation of I B, resulting in nuclear translocation of the Rel/NF-B subunits and activation of transcription. Activated Rel/NF-B subunits are abundantly expressed in RA synovial tissue and in experimental models of arthritis (5)(6)(7)(8)(9). In studies involving experimental arthritis, there is evidence to suggest that the Rel/NF-B subunits play distinct roles in the pathogenesis of inflammatory arthritis (10).…”
mentioning
confidence: 99%
“…NF-B has been detected by immunohistology in human synovial tissue from RA patients during both early and later stages of disease and in both macrophage-and fibroblast-like synoviocytes (15,16). In particular, macrophage-like synoviocytes that localize in the synovial lining layer and the vascular endothelium have been shown to contain p65 and p50 NF-B subunits in their nucleus (16).…”
mentioning
confidence: 99%
“…In particular, macrophage-like synoviocytes that localize in the synovial lining layer and the vascular endothelium have been shown to contain p65 and p50 NF-B subunits in their nucleus (16). This NF-B activation is of functional relevance, since we recently showed that it regulates the expression of TNF␣ as well as other proinflammatory cytokines, such as IL-1␤, IL-6, IL-8, MMP-1 (collagenase 1) and MMP-3 (stromelysin 1), without major effects on the expression of antiinflammatory cytokines IL-10, IL-11, and IL-1 receptor antagonist, soluble TNF receptors, or tissue inhibitor of metalloproteinases 1 (17) in ex vivo synovial membrane cultures.…”
mentioning
confidence: 99%